2017
DOI: 10.1039/c6tb03387c
|View full text |Cite
|
Sign up to set email alerts
|

One ion to rule them all: the combined antibacterial, osteoinductive and anticancer properties of selenite-incorporated hydroxyapatite

Abstract: Although hydroxyapatite (HAp) has been doped with dozens of different ions, the quest for an ion imparting a combination of properties conducive to bone healing is still ongoing. Because of its protean potency and the similarity in size and shape to the phosphate tetrahedron, selenite ion presents a natural ionic substitute in HAp. The incorporation of selenite into synthetic HAp using two different methods – co-precipitation and ion-exchange sorption - was studied for its effect on crystal properties and on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
80
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 85 publications
(84 reference statements)
8
80
0
Order By: Relevance
“…Uskokovic et al [47] confirmed the achievement of a monophasic hydroxyapatite material for samples with concentrations of SeO 3 2− ions ranging from 0.1% to 1.9%. However, the sample with SeO 3 2− concentration of 3% additionally contained reflections from the calcium pyrophosphate phase (β-Ca 2 P 2 O 7 ), which became visible only after calcination at 800 • C. The widening of reflections with increased SeO 3 2− ion content was also noticed [47]. The authors suggest that the decrease in crystallinity with an increase in the content of selenium ions is caused by an uneven dissolution rate in various environments.…”
Section: Powder Diffractometry (Pxrd)mentioning
confidence: 88%
See 4 more Smart Citations
“…Uskokovic et al [47] confirmed the achievement of a monophasic hydroxyapatite material for samples with concentrations of SeO 3 2− ions ranging from 0.1% to 1.9%. However, the sample with SeO 3 2− concentration of 3% additionally contained reflections from the calcium pyrophosphate phase (β-Ca 2 P 2 O 7 ), which became visible only after calcination at 800 • C. The widening of reflections with increased SeO 3 2− ion content was also noticed [47]. The authors suggest that the decrease in crystallinity with an increase in the content of selenium ions is caused by an uneven dissolution rate in various environments.…”
Section: Powder Diffractometry (Pxrd)mentioning
confidence: 88%
“…HA doped with selenium ions can be obtained in two ways: through synthesis, during which ions are incorporated into the HA structure [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47], or by ion exchange, where soaking in a selenium salt solution results in the exchange of ions in the HA structure [47].…”
Section: Synthesis Of Hydroxyapatites Doped With Selenite and Selenatmentioning
confidence: 99%
See 3 more Smart Citations